Islamic Governance as Foreign Policy Identity: Norms, Signaling and International Engagement In Post-2021 Afganistan - Baburi, Sanaullah; Mangesti, Mangesti Waluyo Sedjati; Sadiq Ibrahim Mijinyawa (Hasanuddin Journal of International Affairs, 2026)
The return of the Taliban in August 2021 has positioned Afghanistan at the center of debates on how the international community engages with a governing authority grounded in Islamic principles under conditions of contested legitimacy. This study aims to examine how Islamic governance operates as a foreign policy identity that shapes signaling dynamics, recognition practices, and patterns of international engagement. The paper employs a qualitative conceptual approach by integrating insights from norm contestation, identity-based signaling, and recognition-as-practice, using post-2021 Afghanistan as an analytical reference point. The findings show that Islamic governance generates distinct signaling processes that influence how external actors interpret and respond to political authority, leading to engagement through layered practices such as humanitarian coordination, diplomatic interaction, and security cooperation despite the absence of formal recognition. These interactions produce calibrated forms of engagement that balance normative concerns with practical necessity. The study concludes that governance identity plays a central role in structuring international engagement and provides a framework for understanding how interaction unfolds in a plural and contested global order.